1941
DOI: 10.1103/physrev.60.252
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of the Two-Dimensional Ferromagnet. Part I

Abstract: In an effort to make statistical methods available for the treatment of cooperational phenomena, the Ising model of ferromagnetism is treated by rigorous Boltzmann statistics. A method is developed which yields the partition function as the largest eigenvalue of some finite matrix, as long as the manifold is only one dirnensionally infinite. The method is carried out fully for the linear chain of spins which has no ferromagnetic properties. Then a sequence of finite matrices is found whose largest eigenvalue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
1,171
0
8

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,620 publications
(1,252 citation statements)
references
References 5 publications
32
1,171
0
8
Order By: Relevance
“…The rotational isomeric state (RIS) theory is based on the generator matrix method of Kramers and Wannier [38,39] and was first applied to polymers by Volkenstein (see [40] and refs. therein).…”
Section: Calculation Of Entropic Loss Using Rotational Isomeric Statementioning
confidence: 99%
“…The rotational isomeric state (RIS) theory is based on the generator matrix method of Kramers and Wannier [38,39] and was first applied to polymers by Volkenstein (see [40] and refs. therein).…”
Section: Calculation Of Entropic Loss Using Rotational Isomeric Statementioning
confidence: 99%
“…By the well-known Kramers-Wannier duality [37], the HT graphs form Peierls domain walls [38] separating spin clusters of opposite orientation on the dual lattice. Each bond in a HT graph intersects a nearest neighbor pair on the dual lattice of unlike spins perpendicular to it.…”
Section: Monte Carlo Studymentioning
confidence: 99%
“…On an infinite lattice, the Kramers-Wannier duality implies that observables calculated at an inverse temperature β in the original Ising model can be transcribed to those of the dual model at an inverse temperatureβ. The relation between the two temperatures follows from noting that, an occupied HT bond represents a factor v, while a nearest neighbor pair on the dual lattice of unlike spin on each side of the HT bond carries a Boltzmann weight exp(−2β), so that [37] tanh β = e −2β ,…”
Section: Monte Carlo Studymentioning
confidence: 99%
“…In reference [3] it was shown that the "electric-magnetic" duality of abelian gauge theories allows to describe their physical phase space in terms of a pair of non-local observables that are dual in the Kramers-Wannier sense [4]. The algebra that they obey results to be invariant under spatial diffeomorphisms.…”
Section: Introductionmentioning
confidence: 99%